Optical driven electromechanical transistor based on tunneling effect - Lijie Li (Optics Letters, 2015)
A new electromechanical transistor based on an optical driven vibrational ring structure has been postulated. In the device, optical power excites the ring structure to vibrate, which acts as the shuttle transporting electrons from one electrode to the other forming the transistor. The electrical current of the transistor is adjusted by the optical power. Coupled opto-electro-mechanical simulation has been performed. It is shown from the dynamic analysis that the stable working range of the transistor is much wider than that of the optical wave inside the cavity, i.e., the optical resonance enters nonperiodic states while the mechanical vibration of the ring is still periodic.